General health service readiness and its association with the facility level indicators among primary health care centers and hospitals in Nepal - Kiran Acharya; Yuba R Paudel (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Health care quality has gained unprecedented attention within health systems. In line with the commitments of Government of Nepal's (GoN) 2014 Health Policy and 2015 Constitution of Nepal, GoN is striving to achieve the goal of leaving no one behind with the provision of quality health services. This study aimed to assess health service readiness in hospitals and primary health care centers (PHCCs) of Nepal. # Methods This analysis used data from the 2015 Nepal Health Facility Survey (NHFS), a nationally representative health facility survey that provide information on formal sector health facilities. The data for the analysis for this study was collected using the Inventory Questionnaire collected information on staffing, staff training, infrastructure, medicines, supplies, and services offered in health facilities assessed their service readiness within acceptable standards. The WHO Service Availability and Readiness Assessment (SARA) manual was used to guide the selection of indicators to measure general service readiness. Linear regression analysis was conducted to find the relationship between the facility readiness and the covariates, *ie,* facility level indicators. # Results The average general service readiness score of study facilities in the study was 68.0. No remarkable difference was observed in the mean readiness index of hospitals (government and private). Health facilities in Terai region had low mean readiness score (65.9) compared to those in Mountain (68.1) and Hill (69.9), although no significant difference was detected in multivariate analysis. Province 4 had a significantly higher readiness score than province 1. There is a positive association between the external supervision within 4 months and system of collecting opinion in the facilities with the general service readiness in Nepal. # Conclusions Health facilities had a poorer status on availability of essential medicine, standard precautions for Infection Prevention and diagnostic capacity than for availability of basic equipment and basic amenities. Facilities with external supervision in last 4 months, and facilities having a system of collecting client feedback had higher general service readiness scores. Hence, improving availability of basic inputs (essential medicine, infection prevention, diagnostic capacity) with high priority, and focusing on the external supervision, and client feedbacks are crucial to develop a universally accessible and effective health care for all Nepalese.